Novel compound heterozygous FBXO7 mutations in a family with early onset Parkinson's disease. (November 2020) - Lorenzo-Betancor, Oswaldo; Lin, Yi-Han; Samii, Ali; Jayadev, Suman; Kim, Hojoong M.; Longfellow, Katelan; Distad, B. Jane; Yearout, Dora; Mata, Ignacio F.; Zabetian, Cyrus P.
Abstract: Background: Mutations in the F-box protein 7 ( FBXO7 ) gene result in autosomal recessive parkinsonism. This usually manifests as early-onset parkinsonian-pyramidal syndrome but patients exhibit high phenotypic variability. Here we describe the findings of a Yemeni family with two novel FBXO7 mutations. Methods: Clinical data and DNA were available for three siblings with early-onset parkinsonism together with their parents and three unaffected siblings. A targeted next generation sequencing panel was used to screen the proband for mutations in 14 genes known to cause a parkinsonian disorder. In addition, SNCA, PARK2, PINK1, and PARK7 were screened for copy number variants. Results: The proband carried two novel compound heterozygous FBXO7 mutations: a missense mutation in exon 1 (p.G39R; c.115G > A) and a frameshift mutation in exon 5 (p.L280fs; c.838del). The mutations segregated with disease in the family with the exception of a potentially pre-symptomatic individual whose age was below the age of onset in two of their three affected siblings. P.G39R occurred at a highly conserved amino acid residue and both mutations were predicted to be deleterious in silico. In contrast to most reported families, the phenotype in this pedigree was consistent with clinically typical Parkinson's disease (PD) with a lack of pyramidal signs and good response to dopaminergic therapy. Conclusions: Our study expands the phenotype associated with FBXO7 to include early-onset PD and broadens the list of causative mutations. These data suggest that FBXO7 should be included in clinical genetic testing panels for PD, particularly in patients with early onset or a recessive inheritance pattern. Highlights: Mutations in the FBXO7 gene cause autosomal recessive early-onset parkinsonian-pyramidal syndrome (PPS). We identified a Yemeni family in which three siblings with early-onset parkinsonism shared two novel FBXO7 mutations. Pyramidal signs were lacking and the phenotype was consistent with PD rather than PPS. FBXO7 should be included in genetic testing panels for PD.